DAMPAK SARANA DAN PRASARANA TERHADAP PROSES PEMBELAJARAN DI SEKOLAH DASAR - I Made Sumantara; Ni Nyoman Perni; Ni Nyoman Suastini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe: (1) the strategies used to optimize the role of facilities and infrastructure in improving the quality of student learning; (2) the obstacles faced in the provision and maintenance of facilities and infrastructure; and (3) the implications of the availability of facilities and infrastructure for students in the learning process at SD Negeri 1 Peken Belayu, Tabanan Regency.This study employed a qualitative approach with a descriptive research design. The research subjects consisted of the principal, teachers, and students. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis techniques used the Miles and Huberman model, which included data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation.The results of the study showed that: (1) the strategies implemented by the school and teachers in optimizing facilities and infrastructure included maximizing the use of available facilities, utilizing alternative learning media, and using the surrounding environment as a learning resource; (2) the obstacles faced in the provision and maintenance of facilities and infrastructure included limited school budgets, limited technology-based learning facilities, limited management and maintenance of facilities, and the status of the school land, which is still customary land, thereby hindering access to government development assistance; and (3) the availability of facilities and infrastructure had implications for students’ learning motivation, understanding of learning materials, and activeness in the learning process.